EVALUASI SEISMIK GEDUNG PERKULIAHAN 3 DAN 6 LANTAI EKSISTING DI KOTA YOGYAKARTA - Septhia Irawati, Inggar; Heriawati, Isnaini; Setiawan, Angga Fajar (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2024)
The three-story reinforced concrete building as a college building was built in the city of Yogyakarta in 2011. The building was originally designed to have 6 floors using SNI 1726-2002 and SNI 2847-2002. With the development of construction standards in Indonesia, both regulations have been updated to SNI 1726-2019 and SNI 2847-2019. As a consequence of the updated regulations, re-evaluation of building structures against earthquake loads is important to do. This study aims to evaluate the performance of the existing building structure. The buildings are analyzed under two scenarios: the existing three-story condition and the planned six-story construction according to the Detailed Engineering Design (DED). The analysis employs a nonlinear static procedure based on ASCE 41-23 standards, with seismic load distribution derived from the Indonesian Earthquake Hazard Deaggregation Map. The seismic loading considers two levels of seismic hazard: BSE-1E and BSE-2E. Results indicate that both the three-story and six-story buildings fail to meet the performance criteria stipulated in ASCE 41-23. The evaluation results show that neither the three-story nor the six-story building achieves the Immediate Occupancy (IO) performance level under design earthquake BSE-1E, nor do they meet the Life Safety (LS) performance level under earthquake BSE-2E. Additionally, neither structure meets the maximum allowable horizontal displacement requirements.